PENGARUH PEMBERIAN PUPUK KANDANG KOTORAN AYAM TERHADAP PERTUMBUHAN TANAMAN TOMAT (Lycopercisum esculentum Mill.) - suriani, irma; himayatul asri, indra; Ariandani, Nunung (UNIVERSITAS HAMZANWADI, 2021)
This study aims to determine the effect of giving chicken manure on the growth of tomato (Lycopercisum esculentum Mill). This research was conducted in the village of Bebara, Darmasari Village, Sikur District. This type of research is a quantitative study with an experimental method with a completely randomized research design (CRD). In this study, there were two treatments, namely giving chicken manure (experimental) and without giving chicken manure (control). Where this experiment uses three concentrations, namely 250 grams, 350 grams, and 450 grams, with 4 repetitions. Growth parameters measured were plant height, leaf length and number of leaves. The data analysis technique used is the one-way ANOVA test. The results of hypothesis testing carried out with a significant level of 5% indicate that the plant height F count F table (9,35> 2.92), leaf length F count > F table (12,00 > 2.92), and the number of leaves F count> F table (7,22 > 2.92). Based on the results of the calculation of these data, it can be concluded that the provision of chicken manure can affect the growth of tomato plants (Lycopercisum esculentum Mill) because manure can meet the nutrient needs needed by tomato plants for growth.